SMS Management System for Direct Sales and Network Marketing - Voo, Nyuk Mee; Selamat, Ali (2007)
SMS management system in direct sales and network marketing is a concept of integrating information system with mobile phone as well as using short message service (SMS) as a medium of communication in the business process of direct sales and network marketing sector. Direct sales and network marketing sector is a business phenomenon which expanding rapidly within these few years and it will keep on expanding. To deal with the large members and distributors joining the company, the management of these companies started to seek for new direction in upgrading the relationship management between the company and the distributors. This is important when the low cost and time saving SMS is introduce to these direct selling companies. With the intention of enhancing the connection between distributors is an opportunity to integrate SMS system in the management system in this industry. In this paper, we have analyzed how the SMS will play an important role in the business process by allowing the end user and the company will benefit from its simple and cost saving.